2015
DOI: 10.1016/j.ejim.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

“Multidrug-resistant tuberculosis” may be nontuberculous mycobacteria

Abstract: Introduction Multidrug resistant tuberculosis (MDR-TB) presents a great challenge to public health, especially for developing countries. Some nontuberculous mycobacteria (NTM) cause the similar clinical and radiological characteristics with tuberculosis. We aimed to identify the frequency of NTM infections among subjects who were suspected to have MDR-TB due to lack of response to anti-TB treatment. Methods This retrospective study evaluated patients with suspected MDR-TB due to lack of sputum conversion aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 17 publications
1
56
0
2
Order By: Relevance
“…Some studies suggest that the incidence of NTM is as high as 15.5 cases per 100,000 in persons over 50 years of age in the United States [2-4]. This increase has been attributed to improvements in investigative methodologies such as 16S rNA gene sequencing to detect the presence of mycobacteria and awareness of the importance of NTM species as human pathogens [5,6]. Several studies have attempted to define the phenotypic characteristics of patients with NTM.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggest that the incidence of NTM is as high as 15.5 cases per 100,000 in persons over 50 years of age in the United States [2-4]. This increase has been attributed to improvements in investigative methodologies such as 16S rNA gene sequencing to detect the presence of mycobacteria and awareness of the importance of NTM species as human pathogens [5,6]. Several studies have attempted to define the phenotypic characteristics of patients with NTM.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, clinical symptoms and radiological findings are considered a prerequisite for the diagnosis of NTM pulmonary disease (NTMPD) (2) As NTMPD and TB may be clinically indistinguishable but differ greatly in antimicrobial therapy, a significant added value of detecting NTM lies in the exclusion of TB (3,4). Several cases of MDR-TB misdiagnosis due to NTM infection have been described in areas where NTM are not routinely analyzed (5,6). In countries where they are routinely analyzed, NTM make up a significant share of all mycobacterial laboratory findings and rates are systematically increasing (7,8).…”
mentioning
confidence: 99%
“…Studies conducted in Burkino Faso and Mali found that 18%–20% of patients suspected of having chronic TB were found to have NTM in their sputum ( 6 ). Similarly, a study in Iran showed that as many as 30% of suspected cases of multidrug-resistant TB were in fact NTMs, further suggesting the generalization of this phenomenon ( 7 ). Understanding the true prevalence of NTMs in the developing world is especially valuable considering that evidence suggests that NTM infection may interfere with the Bacille Calmette-Guérin vaccine, a widely used tool in preventing TB infections in the developing world ( 8 ).…”
Section: The Challenges Of Diagnosismentioning
confidence: 96%